2014
DOI: 10.4103/1008-682x.125390
|View full text |Cite
|
Sign up to set email alerts
|

The PCA3 test for guiding repeat biopsy of prostate cancer and its cut-off score: a systematic review and meta-analysis

Abstract: The specificity of prostate-specific antigen (PSA) for early intervention in repeat biopsy is unsatisfactory. Prostate cancer antigen 3 (PCA3) may be more accurate in outcome prediction than other methods for the early detection of prostate cancer (PCa). However, the results were inconsistent in repeated biopsies. Therefore, we performed a systematic review and meta-analysis to evaluate the role of PCA3 in outcome prediction. A systematic bibliographic search was conducted for articles published before April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Six papers 1,15,66,67,70,110 reporting five systematic reviews and meta-analyses were identified which met the inclusion criteria. As data from within-study comparisons were available, these reviews are summarised for completeness in Table 28.…”
Section: Between-study Comparisons: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six papers 1,15,66,67,70,110 reporting five systematic reviews and meta-analyses were identified which met the inclusion criteria. As data from within-study comparisons were available, these reviews are summarised for completeness in Table 28.…”
Section: Between-study Comparisons: Search Resultsmentioning
confidence: 99%
“…Between-study comparisons: summary of systematic reviews Two reviews 66,67,110 assessed the clinical validity of using the PCA3 score to predict prostate cancer. Luo et al 110 considered a repeat biopsy population and included studies without a comparator.…”
Section: Between-study Comparisons: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations